2022
DOI: 10.1021/acsnano.2c00742
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Studies of Single-Nanoparticle-Level Nickel Thermal Oxidation: From Early Oxide Nucleation to Diffusion-Balanced Oxide Thickening

Abstract: High-temperature oxidation mechanisms of metallic nanoparticles have been extensively investigated; however, it is challenging to determine whether the kinetic modeling is applicable at the nanoscale and how the differences in nanoparticle size influence the oxidation mechanisms. In this work, we study thermal oxidation of pristine Ni nanoparticles ranging from 4 to 50 nm in 1 bar 1%O2/N2 at 600 °C using in situ gas-cell environmental transmission electron microscopy. Real-space in situ oxidation videos reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…[21d] The authors showed that the oxidation of Ni started with the formation of an initial NiO thin shell (with 3 nm thickness). Once the Ni/NiO interface had been created, either a single or multiple voids nucleated [36] Copyright 2022, American Chemical Society.…”
Section: Influence Of the Size And Crystal Structure Of The Seedsmentioning
confidence: 99%
See 2 more Smart Citations
“…[21d] The authors showed that the oxidation of Ni started with the formation of an initial NiO thin shell (with 3 nm thickness). Once the Ni/NiO interface had been created, either a single or multiple voids nucleated [36] Copyright 2022, American Chemical Society.…”
Section: Influence Of the Size And Crystal Structure Of The Seedsmentioning
confidence: 99%
“…Sainju et al explored the oxidation kinetics of Ni NCs with different sizes (4‐50 nm) by using in situ gas‐cell environmental TEM (ETEM). [ 36 ] While smaller Ni NCs were entirely oxidized into NiO, larger Ni NCs could be converted only partially, resulting in Ni@NiO core‐shell MSHs. With increases in size, the core‐shell structure changed from symmetric to asymmetric (Figure 7a).…”
Section: From Monometal Seeds To Metal–semiconductor Nanoheterostruct...mentioning
confidence: 99%
See 1 more Smart Citation
“…Information on microstructural evolution and oxidation kinetics can be obtained by in situ TEM studies conducted in an oxidizing environment. 56 Direct observations using in situ gas cell STEM can reveal details such as the evolution of surfaces under oxidation, identifying those surface-specific sites most prone to oxidation, and interfacial and orientation details of the oxide surface. 57 An example of one such study is the analysis of carbon oxidation of a thermal protection system (TPS) material phenolic-impregnated carbon ablator (PICA)�which is composed of carbon fiber preform, FibreForm, and a phenolic resin�used in NASA deep space missions.…”
Section: ■ Applications and Examplesmentioning
confidence: 99%
“…The oxidation of a material can be beneficial by forming a protective coating, or detrimental by corroding the material. Information on microstructural evolution and oxidation kinetics can be obtained by in situ TEM studies conducted in an oxidizing environment …”
Section: Applications and Examplesmentioning
confidence: 99%